Abs. Issue 1 (November 2015) - Hofmann, S.; Bure, I.; Agaimy, A.; Hartmann, A.; Haller, F.; Moskalev, E.
Abstract : Aberrant alterations of DNA methylation patterns have been recognized as early and common events in oncogenesis emphasizing high therapeutic and preventive potential. Concurrent epigenetic silencing of multiple tumour suppressor genes has been reported in different tumours suggesting the existence of a directed program, whereby groups of genes are regulated by promoter methylation. The molecular bases of such a program remain largely unclear. Certain long non-coding RNAs (lncRNAs) have been recently identified that are responsible for target specificity of the histone modification complexes. It remains incompletely understood, however, if lncRNAs may play a role in patterning DNA methylation. In this study, we asked by using gastrointestinal stromal tumours as a model if an epigenetic related HOX Antisense Intergenic RNA, or HOTAIR, is involved in establishment of DNA methylation patterns. To this end, we first showed high up-regulation of HOTAIR in patient samples of high risk compared to low and intermediate risk groups ( n = 66, p = 6.7 × 10 −6 ), what is supported by the earlier reports on common carcinomas. Highest levels of HOTAIR endogenous expression were next detected also in cell lines GIST T1, GIST48b and GIST882. Stable knockdown of HOTAIR was achieved in GIST T1 and GIST48b cells by RNAi using lentiviral transduction. As expected epigenetic alterations due to HOTAIR knockdown could develop with a delay, genome-wide DNA methylation profiling was performed at passage 12 after the transduction on the Infinium HumanMethylation450 BeadChip platform in triplicates. DNA methylation data were analysed by an R package RnBeads. A total of 218 CpG sites got hypomethylated upon HOTAIR knockdown in GIST T1 and GIST48b cells (Δ β > 0.3, FDR < 0.05). These included potential tumour suppressors, transcription factors, tumour-specific antigens, genes related to angiogenesis or involved in metabolism. As confirmed by using bisulfite pyrosequencing for a representative locus, DNA methylation of 64% degree at promoter associated CpG sites of the potential tumour suppressor RASSF1 was almost entirely erased upon HOTAIR knockdown in GIST T1 cell line with concomitant up-regulation detected by qRT-PCR. Concordant with earlier reports, HOTAIR knockdown led to reduced migration potential in GIST T1 cells. Taken together, the results suggest that HOTAIR is one of the factors involved in establishment of specific DNA methylation patterns in GIST. While the molecular mechanism remains to be determined, it is plausible to assume a recruitment of DNA methyltransferases by the Polycomb repressive complex 2, which target specificity is determined by HOTAIR . The results further suggest the feasibility of manipulating DNA methylation patterns in a targeted manner and are of potential interest in context of developing epigenetic cancer therapy. The study is supported by the Interdisciplinary Centre for Clinical Research (IZKF) at the University of Erlangen-Nuremberg.